Leptospira spp. Antibody in Wild Boars (Sus scrofa), Hunting Dogs (Canis lupus familiaris), and Hunters of Brazil - Machado, Fernanda P. (2021)
Hunting activities are a potential risk factor for human infection with Leptospira spp. and, although wild boar seroprevalence has been studied, there are no concurrent serosurveys of wild boars (Sus scrofa), hunting dogs (Canis lupus familiaris), and hunters. The aim of our study was to assess the seroprevalence of Leptospira spp. antibodies in free-ranging wild boars, hunting dogs, and hunters, and risk factors associated with exposure in southern and central-western Brazil. Leptospira spp. antibodies were serologically detected using the microscopic agglutination test, with a total 30 serovars. Overall, 12.2% (9/74) of wild boars and 10.6% (16/170) of hunting dogs were seropositive for at least one serovar and all hunters 0.0% (0/49) were seronegative for Leptospira spp. Seropositivity was statistically higher in 42.1% (8/19) wild boars from natural areas when compared to 2.4% (1/41) from anthropized areas (P<0.001), with prevalence ratio of 17.14 (95% confidence interval: 2.29-128.36). Despite the limited sample size, our findings showed that hunters may be less exposed to Leptospira spp. than are wild boars, particularly in natural areas where Leptospira spp. may be maintained by wild reservoirs. In addition to acting as sentinels, hunting dogs may play a role in disease transmission of sylvatic leptospiral serovars.